How can healthcare organisations improve the social determinants of health for their local communities? Findings from realist-informed case studies among secondary healthcare organisations in England - Luke Munford; Anna Gkiouleka; John Ford; Sam Khavandi; Ruth Watkinson (BMJ Open)
Objectives Increasingly, healthcare and public health strategists invite us to look at healthcare organisations as not just care providers but as anchor institutions (ie, large community-rooted organisations with significant impact in the local economy, social fabric and overall community well-being). In response, this study explores the mechanisms through which healthcare organisations can impact social determinants of health and communities in their local areas.Design We conducted case studies with interviews and synthesised the findings using a realist approach to produce a set of explanations (programme theory) of how healthcare organisations can have a positive impact on the overall well-being of local communities by operating as anchor institutions.Setting Secondary healthcare organisations in England, including mental health and community services.Participants Staff from case study sites which were directly employed or actively engaged in the organisation’s anchor institution strategy. Data collection took place from early June to the end of August 2023.Results We found four building blocks for effective anchor activity including employment, spending, estates and sustainability. Healthcare organisations—as anchor institutions—can improve the social determinants of health for their local communities through enabling accessible paths for local community recruitment and career progression; empowering local businesses to join supply chains boosting income and wealth; transforming organisational spaces into community assets; and supporting local innovation and technology to achieve their sustainability goals. These blocks need to be integrated across organisations on the basis of a population health approach promoted by supportive leadership, and in collaboration with a diverse range of local partners.Conclusions Healthcare organisations have the potential for a positive impact on the overall well-being of local communities. Policymakers should support healthcare organisations to leverage employment, spending, estates and sustainability to help address the unequal distribution of the social determinants of health.